2009
DOI: 10.1016/j.ijgo.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery outcomes from the WHO global survey on maternal and perinatal health in Africa

Abstract: Use of cesarean delivery is limited in the African health facilities surveyed. Emergency cesareans, when performed, are often too late to reduce perinatal deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 14 publications
7
89
2
3
Order By: Relevance
“…According to the WHO Global Survey on Maternal and Perinatal Health, which recently collected CS data in 24 countries around the world [8][9][10], the average frequency of CS in Africa is 9% [11]. Previous studies documenting CS rates among African countries cite a range of 0.6% -18.0% [3,4,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO Global Survey on Maternal and Perinatal Health, which recently collected CS data in 24 countries around the world [8][9][10], the average frequency of CS in Africa is 9% [11]. Previous studies documenting CS rates among African countries cite a range of 0.6% -18.0% [3,4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies documenting CS rates among African countries cite a range of 0.6% -18.0% [3,4,12]. The leading indications for CS in Sub-Saharan Africa (SSA) is labor dystocia followed by previous CS [4,11]. Looking closely at facilities, those with higher CS rates also have higher maternal and neonatal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…38(38%) cases had puerperal pyrexia and 62 (62%) cases were afebrile. Shah A, et al (2009) [16] reported that Cesarean deliveries were performed mostly for cephalopelvic disproportion, dystocia, or failure to progress (median 30.9%); fetal distress (median 25%); previous cesarean (median 21.5%); and malpresentations (median 13.5%) Laparotomy for uterine rupture was uncommon (median 0.08%). Federation of Obstetrical and Gynaecological Societies of India (FOGSI) reported perinatal morality rate 66.30/1000 total births for 1977-79.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that decreasing Caesarean deliveries would have a detrimental effect on mothers and infants' health and patient's choice should be considered [3] . Though, estimates of Caesarean Sections rates in India is 7.1% in the year 1998 but 16.7% change in rates is observed annually in India which is one of highest among the countries of South East Asia region [4] . Various studies have…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study, Berlit et al showed prematurity (OR 2.145, P = 0.024) and silent cardiotocography (OR 0.426, P = 0.038) as a major risk factor for adverse neonatal outcome in emergency CS (16) (16.63 -381.50), P < 0.001] were independently associated with neonatal mortality. In a WHO global survey rate of elective as well as emergency CSs, they were independently associated with neonatal mortality (17).…”
Section: Discussionmentioning
confidence: 99%